JÁNOS JAGAMAS’ FOLK SONG ARRANGEMENTS - PÉTER, Éva (Studia Universitatis Babes-Bolyai Musica, 2020)
The aim of the following study is to present János Jagamas’ vocal folk song arrangements by analyzing the melodies and the compositional methods used within the works. During his scientific work at the Folklore Institute of Cluj-Napoca, the outstanding folk music researcher uncovered and recorded reliable data by collecting, recording, analyzing, and classifying not only Hungarian but also Romanian and Bulgarian melodies. He processed some of the melodies he gathered using a variety of compositional procedures. The works are recommended for children, youth, and amateur choirs, so it is important to get to make them known among music teachers and conductors.